Kasus Pola Tidur dan Performa Fisik pada Mahasiswa Ilmu Keolahragaan Cabang Olahraga Atletik - Rizqi Abdul Fadhli; Ilham Aziz Jaman; Shaleh Fahri; Nabiel Zauama (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to describe sleep patterns and physical performance in Sports Science students majoring in athletics. Sleep patterns were measured using a questionnaire, while physical performance was assessed through a fitness test consisting of a 12-minute run, push-ups, and sit-ups. The results showed that subjects with adequate sleep patterns had optimal physical performance. This study emphasizes the importance of maintaining sleep quality for maintaining fitness and health. However, many student athletes still experience irregular sleep patterns due to their busy training and academic schedules. This condition has the potential to reduce physical performance. Therefore, this study aims to describe the relationship between sleep patterns and physical performance in Sports Science students specializing in athletics.